From Film to Classroom: A Feminist Analysis of Female Characters in “Home Sweet Loan” and Its Implications as Literary Enrichment Material in High School - Azkia Najmi Mumtaza; Yulianeta; Welsi Damayanti (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the role of the main female character in the film Home Sweet Loan based on Naomi Wolf’s liberal feminist principles, which serve as a framework for interpreting the character’s representation, and to examine its implications as literary enrichment material in Indonesian language learning at the senior high school level. The feminist principles are identified through an analysis of the main character’s roles. This study employed a qualitative descriptive method to describe and interpret the meaning of the phenomenon in depth and systematically. The research data consisted of dialogues and scenes involving the main female character in the film Home Sweet Loan (2024). The researcher acted as the primary instrument (human instrument), while data were collected through observation and note-taking techniques. Content analysis was used to examine how the main female character performs various roles in life, which position her in a dual-role context. The findings indicate that the character’s roles can be classified into four domains of life as depicted in the film. From a feminist perspective, these roles reflect the principles of autonomy, equality, and rationality. The main character’s actions represent modern women who strive to determine their own life paths despite operating within a socially gender-biased system. These findings have practical implications for the development of literary enrichment materials in Indonesian language learning at the senior high school level, aligned with the learning outcomes of the Merdeka Curriculum, particularly in fostering students’ critical thinking skills in analyzing gender issues. The film Home Sweet Loan also addresses the limitations of existing literary teaching materials, which are often dominated by patriarchal perspectives, by offering a more contextual and gender-sensitive alternative.